IJCM_162A: Evidence on the Influence of Economic Variables on Breast and Cervical Cancer Treatment in South Asia: Implications for Healthcare Strengthening - A Scoping Review - Dhar Redolen Rose; Rajkhowa Priyobrat; Reshmi Bhageerathy; Holla Ramesh (Wolters Kluwer Medknow Publications, 2024)
Background: Cancer, a leading cause of death globally, imposes a substantial economic burden to the family and family members. This study focuses on the financial aspects of breast and cervical cancer treatments in South Asia, aiming to identify both the direct and indirect costs patients face and the financial barriers and enablers to accessing care. Utilizing the Arksey and O'Malley framework, a scoping review of literature from 2006 onward was conducted, examining costs associated with treatment modalities like radiotherapy, chemotherapy, and surgery for breast and cervical cancer. Results: Analysis of 192 records led to 12 studies being reviewed in detail. Results showed that treatment costs for cervical cancer ranged from INR 19,494 to 41,388 (USD 291 - 617), with about 62% of patients incurring catastrophic health expenditures. Breast cancer treatment also proved costly, with expenses ranging widely but averaging around Rs. 48,477. Such high out-of-pocket costs not only pose a significant financial challenge for patients but also threaten the effectiveness of international health initiatives aimed at cancer treatment and management. Conclusion: The study concludes that the financial burden of breast and cervical cancer treatments in South Asia is significant, highlighting the urgent need for healthcare systems to mitigate these costs. Enhancing support for both medical and non-medical expenses is essential for reducing financial strain on patients, ensuring equitable access to treatments, and advancing towards the goals of global healthcare initiatives.